1402. Smart Technology and Education for Smart Protection against the Flu: Impact of a Multifaceted Quality Improvement (QI) Intervention on Influenza Vaccination Rates in Children. (31st December 2020) - Kaushik, Ashlesha; Beal, Kristen; Gupta, Sandeep; Malley, Richard
Abstract: Background: Low pediatric influenza vaccination rates are a public health challenge. It is imperative that innovative measures to promote influenza immunization are studied. Methods: Aim: To study impact of a multifaceted QI intervention on influenza vaccination rates in children evaluated at outpatient clinics, urgent care (UC) and emergency departments (ED) at UnityPoint Health tertiary care centers (UPH) across Northwestern (NW) and Northcentral (NC) Iowa (IA). Patients aged 6 months-18 years evaluated at UPH in NW and NC IA (encompassing 5 outpatient clinics, 2 UC, 2 ED) were included. A multifaceted QI intervention was implemented on 9/1/2018 consisting of all of the following concomitantly: 1. Patient/family education: Posters about flu vaccination displayed at entrance, in waiting rooms and patient rooms throughout the clinics, UC, ED as well as patient/family handouts emphasizing importance of influenza immunization. 2. Information Technology: "Health maintenance" reminder in outpatient electronic medical record (EMR- EPIC) that appears as soon as a patient's chart is accessed to remind nurses/providers that influenza vaccine is due. 3. Provider Education flyers at study sites about debunking flu myths. We compared pre-intervention period (P1, 09/01/2017– 05/31/2018) with intervention period (P2, 09/01/2018 – 05/31/2019) for influenza vaccination rates. Results: A total of 10050 and 9889 patients were evaluated during P1 and P2 respectively. Influenza vaccination rate increased significantly from 56.1% (5642) in P1 to 73.3% (7252) in P2 (p< 0.0001). Patients were 1.43 times more likely to get vaccinated during P2 than P1 (95% CI= 1.32-1.46). Regionally during P2, influenza vaccination rate was higher than the national (62.6%; p< 0.0001) and Iowa state averages (65.8%; p< 0.0001) respectively. Proportion of children aged < 9 years receiving second dose of influenza vaccine increased from 43% to 69% (p< 0.001). Influenza vaccination rates among children aged 6-36 months increased significantly [40% (1078/2671) in P1 to 47.2% (1287/2723) in P2; p< 0.01]. Conclusion: With the combined educational and technologic intervention, pediatric influenza vaccination rates increased significantly across NW and NC IA, including proportion of patients receiving second dose of the vaccine. Disclosures: Richard Malley, MD, Merck (Consultant)